Univerzitetna biblioteka v Ljubljani - Kodrič-Dačić, Eva (Knjižnica, 2005)
The article presents the history of the National and University Library from the period 1938 to 1943. The period begins in 1938 when the former State Studium Library became a part of the University of King Alexander I and changed its name to University Library, and ends with the collapse of the fascist Italy in 1943. After more than 150 years the Library lost its independent status and became fully subordinated to the University. At the very beginning of the Second World War it moved into the new library building. It had to adapt to the war conditions and cope with the requirements of the Italian occupation authorities.
Keywords: Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana; nacionalne knjižnice; 1938/1943; zgodovinski pregledi